Current spectrum and outcomes of infarct-related cardiogenic shock: insights from the CULPRIT-SHOCK registry and randomized controlled trial - Zeymer, Uwe; Heer, Tobias; Ouarrak, Taoufik; Akın, Ibrahim; Noc, Marko; Stepinska, Janina; Oldroyd, Keith; Serpytis, Pranas; Montalescot, Giles; Huber, Kurt; Windecker, Stephan; Savonitto, Stefano; et al. (European heart journal - acute cardiovascular care, 2024)
We analysed consecutive patients with acute myocardial infarction complicated by cardiogenic shock (CS) who were enrolled into the CULPRIT-SHOCK randomized controlled trial (RCT) and those with exclusion criteria who were included into the accompanying registry.In total, 1075 patients with infarct-related CS were screened for CULPRIT-SHOCK in 83 specialized centres in Europe; 369 of them had exclusion criteria for the RCT and were enrolled into the registry. Patients were followed over 1 year. The mean age was 68 years and 260 (25%) were women. 13.5%, 30.9%, and 55.6% had one-vessel, two-vessel, and three-vessel coronary artery disease (CAD), respectively. Significant left main (LM) coronary artery stenosis was present in 8.0%. 54.2% of the patients had cardiac arrest before admission. Thrombolysis in myocardial infarction (TIMI) 3 patency of the infarct vessel after percutaneous coronary intervention was achieved in 83.6% of all patients. Mechanical circulatory support was applied in one-third of patients. Total mortality after 30 days and 1 year was 47.6% and 52.9%. Mortality after 1 year was highest in patients with LM coronary artery stenosis (63.5%), followed by three-vessel (56.6%), two-vessel (49.8%), and one-vessel CAD (38.6%), respectively. Mechanical complications were rare (21/1008; 2.1%) but associated with a high mortality of 66.7% after 1 year.In specialized centres in Europe, short- and long-term mortality of patients with infarct-related CS treated with an invasive strategy is still high and mainly depends on the extent of CAD. Therefore, there is still a need for improvement of care to improve the prognosis of infarct-related CS.
Veröffentlicht: 13. Februar 2024
Gesehen am 23.08.2024